2009
DOI: 10.1074/jbc.m109.031971
|View full text |Cite
|
Sign up to set email alerts
|

Adult Ceramide Synthase 2 (CERS2)-deficient Mice Exhibit Myelin Sheath Defects, Cerebellar Degeneration, and Hepatocarcinomas

Abstract: (Dihydro)ceramide synthase 2 (cers2, formerly called lass2) is the most abundantly expressed member of the ceramide synthase gene family, which includes six isoforms in mice. CERS2 activity has been reported to be specific toward very long fatty acid residues (C22-C24). In order to study the biological role of CERS2, we have inactivated its coding region in transgenic mice using gene-trapped embryonic stem cells that express lacZ reporter DNA under control of the cers2 promoter. The resulting mice lack ceramid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
272
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 267 publications
(294 citation statements)
references
References 33 publications
21
272
1
Order By: Relevance
“…S7). CERS2 is known to be important for C24 Cer synthesis (3,22). Both of the reactions inhibited by FB 1 or CERS2 siRNA, i.e., the elongations of C20:0-and C22:0-CoAs, are essential for the production of C24-CoA, the CERS2 substrate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S7). CERS2 is known to be important for C24 Cer synthesis (3,22). Both of the reactions inhibited by FB 1 or CERS2 siRNA, i.e., the elongations of C20:0-and C22:0-CoAs, are essential for the production of C24-CoA, the CERS2 substrate.…”
Section: Resultsmentioning
confidence: 99%
“…5). A recent report analyzing CerS2 knockout mice revealed that a deficiency in C24 sphingolipid synthesis results in myelin sheath defects, cerebellar degeneration, and hepatopathy (3,11). Moreover, the VLCFA moiety of sphingolipids may be important for determination in molecular species of sphingolipids, because C24 FAs are used in the gangliosides GM3 and GD3 but not in other gangliosides with more complex sugar structures (27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations